The Effect of An Educational Approach According to the (Stand) Strategy in Learning Some Basic Skills in Volleyball and Keeping Them in The Misan Education Team - Hussein Farhan Sheikh Ali; Yasser Mohsen Aliwi; Wissam Qais Khazal (Zien Journals, 2022)
This study was done to determine the influence of Student Teams Achievement Division (STAD) strategy on volleyball skills and their retention. This study also sought to determine the distinction between the effects of mathematics communication and retention of certain volleyball skills and the interplay of STAD strategy skills in high school team. The sort of research employed was experimental research with a quasiexperimental design as the research design. Random sampling was utilized to acquire two sample classes, namely the experimental class X F with nine students and the control class X A with nine students of class X pupils in the Directorate of Misan Education team during the 2018-2019 school year. The experimental class utilized the STAD strategy, while the control class utilized the strategy. The duration of the experimental learning was three meetings plus one examination meeting. Two-way ANOVA with unequal cells was utilized to determine the conclusion of the examination. Implementing the STAD technique and learning and preserving the precision of certain volleyball abilities had an influence, according to the findings. The STAD technique resulted in superior volleyball learning outcomes compared to the Traditional strategy. In addition, high-level volleyball abilities and their retention were superior than medium and low levels. There was no correlation between acquiring volleyball strategy and skills and their retention
Keywords: Curriculum; Strategy; Volleyball